The Effect of Using the Student Academic Ability- Problem Solving and 5E Cycle Learning Models on the Student Learning Outcomes - Yayat Mutia Ardi; Vauzia Vauzia; Abdul Razak; Syamsurizal Syamsurizal (Postgraduate, University of Mataram, 2021)
Education in the 21st century aims to change the learning paradigm from teacher-centered to student-centered in order to improve student learning outcomes. Hence, a learning model is needed to improve the students' ability to solve problems by paying attention to their academic ability. This study aims to determine the effect of using the student academic ability-based problem solving and 5E cycle learning models on the student learning outcomes in addictive materials and addictive substances. This study used an experimental method with a 2x2 factorial design. The population in this study was all students of grade VIII SMPN 18 Padang. This study's sample was chosen using the purposive sampling technique, the data collection techniques for the student learning outcomes used to test techniques at the end of learning. The data analysis was performed by using the prerequisite tests (normality and homogeneity tests) and the hypothesis tests using 2-way ANOVA and continued with Bonferroni advanced test. The results show that:Â There is an interaction between the problem-solving model and the academic ability-based 5E Cycle learning model on the student learning outcomes, but there is no significant difference in learning outcomes between the problem-solving model and the 5E learning cycle model. There is an effect on the academic ability towards the student learning outcomes. There is no difference in the student learning outcomes between students with high academic ability in the two sample classes. There is no difference between the students with low academic ability in the two sample classes.